PENGARUH NON PERFORMING FINANCING (NPF) DAN FINANCING TO DEPOSIT RASIO (FDR) TERHADAP RETURN ON ASSET (ROA) PADA PT BANK PANIN DUBAI SYARIAH Tbk TAHUN 2012-2021 - Fazriah, Nurul; Hidayat, Arif (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Non Performing Financing and Financing to Deposit Ratio on Return On Assets at PT Bank Panin Dubai Syariah Tbk. The data used is the quarterly financial report of PT Bank Panin Dubai Syariah Tbk for the period 2012-2021. This research uses quantitative research with causal associative research methods and processing using SPSS Version 29. The data analysis techniques used are multiple regression tests and hypothesis tests, t tests to test coefficients partially and F tests to simultaneously test the influence together with significance level 5% and Determination test. During the observation period, it shows that the research data is normally distributed. Based on the normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, no variables were found that deviated from classical assumptions. This shows that the available data meets the requirements for using a multiple linear regression equation model. The results of this research are that NPF has an effect on ROA while FDR has no effect on ROA. Simultaneously NPF and FDR influence ROA. The coefficient of determination value is 62.5% of ROA, while the remaining 37.5% is influenced by other variables.